Lavoro, consumo e tempo libero nelle pratiche informali di riciclo alimentare. Il reciclaje nella città di Granada (Spagna) - Giorgio Cassone (Archivio Antropologico Mediterraneo)
This paper analyses informal food-recycling practices: the research, reclamation, circulation, and consumption of food rejected from the urban food cycle and the transformation of garbage into an edible and familiar object. Every day, informal food-recyclers play with the urban space according to the constraints and opportunities that the city offers them. Rigorous observation of their practices reveals that they develop specific knowledge that is functional to the practice of salvaging food. Skills are mobilized to decode and explore the city and its activities; to interact with actors and norms; to reclaim and transform food used not only for nutrition but also as a social resource for creating and consolidating groups around food-sharing. So, moments and spaces of survival become also moments and spaces for innovation where skills, abilities and knowledge related to food-recycling circulate, are transformed and reproduced collectively within these groups. Thus, the informal network becomes the means of transmission of transferable skills, strengths and potentials and provides to individuals a support and even protects, socializes and promotes inclusion in a specific group. In this context, food-recycling practices appear as daily tactical practices, aimed at maintaining individual and “activist” groups, in which the production and reproduction of solidarity and sharing networks define moral economies parallel to market’s economy.